2021
DOI: 10.1051/0004-6361/202038955
|View full text |Cite
|
Sign up to set email alerts
|

ALMA resolves giant molecular clouds in a tidal dwarf galaxy

Abstract: Tidal dwarf galaxies (TDGs) are gravitationally bound condensations of gas and stars formed during galaxy interactions. Here we present multi-configuration ALMA observations of J1023+1952, a TDG in the interacting system Arp 94, where we resolve CO(2-1) emission down to giant molecular clouds (GMCs) at 0.64 ∼ 45 pc resolution. We find a remarkably high fraction of extended molecular emission (∼80−90%), which is filtered out by the interferometer and likely traces diffuse gas. We detect 111 GMCs that give a sim… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 125 publications
3
16
0
Order By: Relevance
“…CO observations with the Atacama Large Millimeter/ submillimeter Array (ALMA) have successfully made detections of individual clumps of molecular gas in the wakes of ram-pressure-stripped galaxies (e.g., Jáchym et al 2019) as well as individual giant molecular clouds in TDGs (Querejeta et al 2021). If BCs still contain significant quantities of molecular gas (as would be expected based on their recent SF), then they should be readily detectable with ALMA, especially as their high metallicity measurements imply a favorable CO-to-H 2 conversion factor in comparison to other low-mass objects (Bolatto et al 2013).…”
Section: Future Directionsmentioning
confidence: 99%
“…CO observations with the Atacama Large Millimeter/ submillimeter Array (ALMA) have successfully made detections of individual clumps of molecular gas in the wakes of ram-pressure-stripped galaxies (e.g., Jáchym et al 2019) as well as individual giant molecular clouds in TDGs (Querejeta et al 2021). If BCs still contain significant quantities of molecular gas (as would be expected based on their recent SF), then they should be readily detectable with ALMA, especially as their high metallicity measurements imply a favorable CO-to-H 2 conversion factor in comparison to other low-mass objects (Bolatto et al 2013).…”
Section: Future Directionsmentioning
confidence: 99%
“…In addition, there could be plausible variations in the line ratio 𝑅 21 . Multi-transition CO observations have shown that 𝑅 21 can vary from ∼0.3 to ∼1.5 in typical spiral galaxies (Leroy et al 2009;Querejeta et al 2021;Den Brok et al 2021). Interestingly, in the Seyfert prototype NGC 1068, the value of 𝑅 21 ranges from 1.6 to 2.5 (Viti et al 2014).…”
Section: Implications For the Co-to-h 2 Conversion Factormentioning
confidence: 99%
“…As TDGs are recycled objects, they inherit their parent galaxies' metallicity, making CO a suitable molecular gas tracer for comparison with nearby disk galaxies (e.g., Duc et al 2000). Previous CO observations toward TDGs have shown that molecular gas is abundant in TDGs (e.g., Braine et al 2000Braine et al , 2001Lisenfeld et al 2002Lisenfeld et al , 2004Lisenfeld et al , 2008Lisenfeld et al , 2016Duc et al 2007;Boquien et al 2011;Querejeta et al 2021;Kovakkuni et al 2023). Whether the molecular K-S relation (i.e., H 2 S versus Σ SFR ) of the TDGs is consistent with that in the disk galaxies is under debate.…”
Section: Introductionmentioning
confidence: 99%
“…Braine et al (2001) = S S ) in the TDGs is comparable to that in spiral galaxies. On the other hand, TDGs that do not follow the molecular K-S relation of normal disk galaxies have been found (Lisenfeld et al 2008(Lisenfeld et al , 2016Querejeta et al 2021;Kovakkuni et al 2023), suggesting a diversity of SFE H 2 in TDGs. In particular, Querejeta et al (2021) reported that there are regions in tails where star formation is severely suppressed despite the presence of large amounts of molecular gas.…”
Section: Introductionmentioning
confidence: 99%